Design and development of an LADM-driven 3D Land administration system: Lessons learned in Malaysia. (March 2021) - Rajabifard, Abbas; Atazadeh, Behnam; Kalantari, Mohsen; Olfat, Hamed; Shojaei, Davood; Badiee, Farshad
Highlights: The transformation from 2D to 3D cadastral database should be in accordance with a standard-based approach. This study aims to design and develop an LADM-driven 3D land administration system for Malaysia. Malaysian land administration infrastructure is ready for an upgrade to include 3D digital data. Current workflows should be modified to support the realization of LADM-based 3D land administration in Malaysia. Abstract: Urban infrastructure has been dramatically increasing in Malaysian cities over the last decades. The current 2D-based practices are challenged by the stratified development of urban land in underground and aboveground areas. Currently, in Malaysia, surveying measurements are stored in a 2D-based cadastral database in the form of horizontal coordinates. However, this method is not capable to accommodate ownership complexities in the vertical dimension. The existing methods to capture, compute and adjust cadastral survey data need to be upgraded for the purpose of implementing a 3D land administration system (LAS) in Malaysia. The transformation from 2D to 3D LAS should be in accordance with a standard-based approach. Land Administration Domain Model (LADM): ISO 19152:2012 provides an internationally accepted standard model for recording and managing cadastral data. This study aims to design and develop an LADM-driven 3D LAS for Malaysia by building on existing research carried out for LADM adoption in this country. The proposed approach includes modifications in the existing workflows for capturing 3D survey data, new architecture to support 3D land parcels, and a new database for creating an LADM-based 3D LAS in line with data requirements in Malaysia. The major part of the upgrade from 2D to a 3D environment consists of capturing, processing and management of height of survey points that define parcel boundaries. This study demonstrated and confirmed that the LADM standard plays a significant role in realising a 3D-enabled system for Malaysian land administration.